Factors related to earthquake preparedness of households based on social-cognitive theory constructs: A systematic review - Rezabeigi Davarani, Esmat; Nekoei-Moghadam, Mahmood; Khanjani, Narges; Iranpour, Abedin; Chashmyazdan, Mohammadreza; Farahmandnia, Hojjat (Frontiers in Public Health, 2023)
Background Earthquakes cause many casualties worldwide. Taking preventive measures and improving community preparedness is critical to reducing earthquake damage. The social cognitive theory explains how individual and environmental factors cause behavior. This review was conducted to identify the social cognitive theory structures, in research on the preparedness of households against earthquakes. Materials and methods This systematic review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search was conducted from January 1, 2000, to October 30, 2021 in Web of Science, Scopus, PubMed, and Google Scholar. Studies were selected based on inclusion and exclusion criteria. The initial search yielded 9,225 articles, and finally, 18 articles were selected. Articles were assessed using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist. Results Eighteen articles about disaster preparedness behaviors based on the socio-cognitive constructs were identified and reviewed. The essential constructs used in the reviewed studies included self-efficacy, collective efficacy, knowledge, outcome expectations, social support, and normative beliefs. Conclusion By identifying the dominant structures that have been used in studies related to the preparedness of households against earthquakes, researchers can implement appropriate and more cost-effective interventions by focusing on improving suitable structures.